2021
DOI: 10.17759/chp.2021170114
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Competence as a Predictor of Adaptation of Foreign Students

Abstract: The aim of the study is to determine the role of intercultural competence in the adaptation process of foreign students studying at Russian universities. The research is based on the author's model of intercultural competence, the main components of which are intercultural stability, intercultural interest, the lack of ethnocentrism and the management of intercultural interaction. The sample of the study consisted of 291 foreign students from Turkmenistan studying at universities in Kazan, Saratov, Penza, Rost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…By taking adaptation measures for students from other countries, we can minimize the risk of their maladjustment and help them integrate into the Russian educational space [Gritsenko et al 2021]. According to D. S. Tretyachenko, faculty members at Russian universities need to develop special pedagogical competencies in the socio-cultural adaptation of foreign students [Tretyachenko 2021].…”
Section: Psychology Of Interethnic Differences and Inter Action: Rele...mentioning
confidence: 99%
“…By taking adaptation measures for students from other countries, we can minimize the risk of their maladjustment and help them integrate into the Russian educational space [Gritsenko et al 2021]. According to D. S. Tretyachenko, faculty members at Russian universities need to develop special pedagogical competencies in the socio-cultural adaptation of foreign students [Tretyachenko 2021].…”
Section: Psychology Of Interethnic Differences and Inter Action: Rele...mentioning
confidence: 99%
“…Russian versions of The Intergroup Anxiety and The Intercultural Communication Effectiveness scales have been tested in previous studies in Russia and found to have adequate validity and reliability (Gritsenko et al, 2021;Khukhlaev and Bratkina, 2021).…”
Section: Measurementsmentioning
confidence: 99%
“…There are numerous studies on the factors and predictors of the effectiveness of intercultural communication among international students in a new socio-cultural environment, including socio-demographic characteristics, health status, personality traits, tolerance, identity, metastereotypes, cognitive abilities, intercultural competence; cultural intelligence, and so on (Güngör and Bornstein, 2009;de Araujo, 2011;Neuliep, 2012;Jenny, 2013;Bücker et al, 2014;Bierwiaczonek and Waldzus, 2016;Presbitero and Attar, 2018;Thomas, 2018;Solhaug and Kristensen, 2020;Gritsenko et al, 2021;Ma and Xia, 2021;Matera and Catania, 2021;Cao and Meng, 2022;Xiong et al, 2022). The listed variables have a different impact on intercultural communication depending on external and internal conditions, which in turn sets the task of finding new predictors of the effectiveness of intercultural communication among international students.…”
mentioning
confidence: 99%
“…Many people find it difficult to adjust to new environment or host environment. Therefore, it is necessary to cultivate the crosscultural ability of the students in oversea or internasional student di China [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%